Yüksek Eğitimli Uzman Hemşire İstihdamı ile Acil Servislerde Hizmet Kalitesinin Yükseltilmesi için Simülasyon Uygulaması: Türkiye Sağlık Sistemi - DÖNMEZ, CEM ÇAĞRI (My University, 2018)
Acil servisler sağlık sistemin temel yapı taşını oluşturmaktadır. Bu çalışmada Türkiye’deki acil servislerin çalışma sistemleri incelenerek,acil servislerdeki problemler dikkate alınmıştır. Özellikle metropol şehirlerde acil servislerdeki yoğunluk ölçülemez haldedir. Bunun başlıcanedeni acil servislere gelen çoğu hastanın acil diye nitelendirilen bir sağlık sorununun bulunmamasıdır. Bu durum, hastaların beklemeve hastanede kalış sürelerinin çok uzun olmasına ve tedavi edilen hasta sayısının azalmasına neden olmaktadır. Bu çalışma ile acil servislerdeacil olmayan ya da ayakta tedavi edilebilecek olan hastaların yüksek eğitimli uzman hemşireler istihdamı ile tedavi edilerek hastanedekibekleme süresinin azaltılması amaçlanmıştır. 1/24 (günlük) ve 7/24 (haftalık) çalışma esasına göre uygulanan kesikli-olay simülasyonörneği ile YUH istihdamı sağlanarak tedavi edilen hasta sayısında, 1/24 esasına göre %26,71 ve 7/24 esasına göre %15,13 oranındaartış sağlandığı görülmüştür. Hastaların acil servise kayıt yaptıkları andan itibaren tedavi olmak için bekledikleri süre 1/24 esasına göre%38,67 ve 7/24 esasına göre %53,66 oranlarında iyileşme sağlanarak bekleme süresi kısaltılmıştır. Aynı şekilde bir hastanın tedavi olmakiçin acil servislerde geçirmesi gereken süre ortalama 82,46 dakikadan 53,97dakikaya düşürülmüştür. Bulgular arasında, acil servislerde istihdamedilen kaynaklardan yeteri kadar verim alınamamasıyla YUH istihdamı sayesinde kaynaklara ait verimlilik oranlarında bir dengesağlandığı görülmüştür. Ek olarak, YUH istihdamı ile doktorların çalışma yoğunluklarının azaldığı tespit edilmiştir.

Emergency departments are the cornerstones of the healthcare systems. However, emergency services are not able to do their primary duty. This is mainly due to the fact that most of the patients who come to the emergency department do not have any serious health problem defined as emergency. This study examined the working system of emergency services in Turkey. Especially, in metropolitan cities the intensity in emergency services is becoming immeasurable. This situation causes the waiting time of the patients to be excessive. This research aimed to decrease the waiting time of the patients by being treated by high-educated specialist nurses (HSN) in the emergency departments that are not urgent or outpatient. HSN, as a different healthcare employee class, has been proposed to treat patients who are engaged in emergency services but in fact whose health status is not urgent. A discrete event simulation approach was applied to obtain tangible results with real numerical data. Strategies or scenarios that are expected to occur in normal life not only require high costs but also need a lot of time. In such studies, simulation applications enable to get results in a faster and shorter time. Otherwise, both higher budget and time are needed in the studies that require application to put it into practice. Therefore, it is indispensable for researchers to make simulation applications which need short time and low cost but give low margin of error. In this study, a three-dimensional simulation model has been developed with two scenarios for the emergency department. In these scenarios, the number of treated patients, the waiting time of the patients, the duration of the patients in the emergency department, and the utilization rates of resources of emergency department were compared. With the help of developed patient flow chart, the patient is examined in the triage area by HSN after the normal triage procedure and then is exited or referred to polyclinic if needed. The patient, who was examined by HSN, is no longer examined by the doctor again unless necessary. The patient is referred to the doctor according to the urgency and type of disease, and after the doctor’s examination, referral or outpatient referrals are carried out. In this case, not all the patients will have to wait for their doctor. According to the discrete-event simulation example applied on 1/24 and 7/24 basis, it was observed that the number of patients treated by providing employment of HSN was increased by 26,71% on the basis of 1/24 and 15,13% on the basis of 7/24. The waiting time for treatment was reduced by 38.67% on 1/24 basis and 53.66% on 7/24 basis, respectively, from the time the patients were enrolled in emergency services. In the literature data, the rate of check in to emergency services of patients who do not have an emergency situation is usually above 50%. The lowest rate of patient waiting time was estimated as 50% (Physician) / 50% (HSN) on a 1/24 basis and 40% (Physician) / 60% (HSN) on a 7/24 basis. The time required for a patient to be treated in emergency services for treatment was reduced from an average of 82.46 minutes to 53.97 minutes. Among the findings, it has been seen that the efficiency of the employment of HSN has provided a balance in the efficiency rates of the resources by not getting the efficiency as high as the resources employed in the emergency services. In addition, it has been found that the employment intensity of physicians decreases with the employment of HSN. In accordance with these results, it is observed that the HSN employment and the productivity ratios of the resources are balanced. In brief, the aim of this study is to improve the structure and the quality of the healthcare system and to increase the patient satisfaction. For this purpose, it is proposed to increase the authority and activity of the nurses in the healthcare system. The results obtained emphasize the accuracy and validity of this objective. As a result, emergency services in the healthcare system of Turkey should be reinforced with HSN employment by the government. With this recommendation, it will help to reduce the intensity of emergency services and to make the resources used more efficient. This study consists of five parts. In the first part, information about the function of the emergency services and the types of nurses in the healthcare system are provided. The second part contains a literature review of the methods developed and applied for the solution of problems in the healthcare sector. In the third part, there is a description of the method of this study. The identification of the patient flow chart and data required for the creation of the simulation model is made in this section. The construction and operation of the simulation model is included in this part. In the fourth section, simulation results are compared and discussed. In the last part, the conclusion and a brief review of the study are involved.
Implementation of Simulation to Increase Emergency Department Service Quality with High – Educated Specialist Nurses Employment: Turkish Health System
Keywords: Acil Tıp; Sağlık Bilimleri ve Hizmetleri; Tıbbi İnformatik